PENERAPAN BISNIS MODEL KANVAS DALAM PENENTUAN RENCANA MANAJEMEN USAHA KEDELAI EDAMAME GORENG - Novitha Herawati; Triana Lindriati; Ida Bagus Suryaningrat (Faculty of Agricultural Technology, University of Jember, 2019)
Business model canvas (BMC) is a strategic management and lean start-up template for developing new or documenting existing business models. It is a visual chart with elements describing a firm's or product's value proposition, infrastructure, customers, and finances. It assists firms in their aligning activities by illustrating potential trade-offs. Business model canvas focuses on the idea of creating value in a business. The purpose of implementation of BMC was to determined the best business planning of fried edamame, when it applied to the industry or MSMEs (Micro, Small and Medium Enterprises). The method in the research used descriptive method, while the data analysis used qualitative analysis. Primary data collection was obtained from interviews. Analysis was done by compiling the initial hypothesis, hypothesis testing and verification of business model canvas (BMC). The results showed that the business model strategy for fried edamame products in the value proposition component were crispy, natural, labeled and applied good cooking oil for use. The customer segment component were the buyers of the entire Jember Regency including men and women over 20 years old with middle income. Components of revenue streams were fried edamame product sales, sale of unused oil, and sale of edamame peel to farmers, while the component channels were direct selling and retailers for fried edamame product. Keywords: business model, fried edamame, strategy, value proposition